2021
DOI: 10.3390/antibiotics10060719
|View full text |Cite
|
Sign up to set email alerts
|

Finding a Balance in the Vaginal Microbiome: How Do We Treat and Prevent the Occurrence of Bacterial Vaginosis?

Abstract: Bacterial vaginosis (BV) has been reported in one-third of women worldwide at different life stages, due to the complex balance in the ecology of the vaginal microbiota. It is a common cause of abnormal vaginal discharge and is associated with other health issues. Since the first description of anaerobic microbes associated with BV like Gardnerella vaginalis in the 1950s, researchers have stepped up the game by incorporating advanced molecular tools to monitor and evaluate the extent of dysbiosis within the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 292 publications
(360 reference statements)
0
33
0
Order By: Relevance
“…Bacterial vaginosis is caused by imbalance in the ecology of the vaginal microbiota, and approximately one-third of women worldwide have suffered to BV at different times in their lives [101] . Probiotics are considered an effective treatment to increase the Lactobacillus colonization rate and restore the normal flora in the vagina, thus helping to alleviate vaginal inflammation.…”
Section: Female Reproductive Microbiomementioning
confidence: 99%
“…Bacterial vaginosis is caused by imbalance in the ecology of the vaginal microbiota, and approximately one-third of women worldwide have suffered to BV at different times in their lives [101] . Probiotics are considered an effective treatment to increase the Lactobacillus colonization rate and restore the normal flora in the vagina, thus helping to alleviate vaginal inflammation.…”
Section: Female Reproductive Microbiomementioning
confidence: 99%
“…It is important to note that many clinical trials examine the use of probiotics as a supplementation to conventional therapy against infectious diseases, such as antibiotic and antifungal agents ( Shi et al, 2019 ; Joseph et al, 2021 ). In general terms, probiotics have shown effectiveness in preventing infectious diseases in different organ systems, from the respiratory and gastrointestinal tracts to the female urogenital system, among others.…”
Section: Probioticsmentioning
confidence: 99%
“…Clinical symptoms of BV include (1) vaginal pH > 4.5, (2) grayish-white vaginal discharge with a (3) distinct fishy odor due to the presence of polyamines, and (4) detection of clue cells (epithelial cells covered with Gram-negative rod cells) in the vaginal smears examined under the microscope. Limited studies have examined the mechanistic details of how N. gonorrhoeae responds to the healthy and dysbiotic vaginal ecology and how this could potentially impact treatment and vaccine development [ 129 , 130 , 131 ]. In vitro studies have shown that N. gonorrhoeae responds to acidic conditions by modulating the expression of surface-expressed proteins including Rmp, an important determinant of gonococcal vaccine efficacy, and stress response proteins Hsp63 [ 132 , 133 , 134 ].…”
Section: Interactions Between N Gonorrhoeae and Th...mentioning
confidence: 99%